As competências profissionais demonstradas pelos egressos de administração da Universidade Federal do Ceará oriundos de programas de estágio - Morais, Diana Maria Cavalcante (2008)
Based on the apprenticeship and its relation with the development of professional competences, this study was ruled by three guiding questions: 1) What are the competences acquired or developed by the former students of Administration derived from the apprenticeship programs? 2) How much has the apprenticeship contributed to improve the professional competences? 3) Which of these competences, in the Administration course, match the National Curricular Rules? Based on these questions, this study had as its main objective to verify in the conception of former students from the Administration course in the Federal University of Ceará, which competences and how much they were developed during the programs of apprenticeship, and which of them were agreed with the National Curricular Rules. Its relevance consists of approaching and contributing with modern themes such as apprenticeship and competence, through the former students in Administration view who had undergone the apprenticeships. The present study had an exploratory and descriptive characteristic. The bibliographical research approached issues related to education and work, as well as competences and students‟ apprenticeship. The field research involved 40 former students that had finished their courses in the following years: 2005, 2006, and 2007. In the process of data collection, a structures and anonymous questionnaire was used as a tool. Excel program was used as a support to data analysis. The research results allowed us to conclude that the apprenticeship contribute to approximate the relation between theory and practice as well as to develop competences that are important to the Professional formation, insertion and permanence into the working market and the development of the career too.